Broadening assessable domains: Lessons learnt from the development of a wellbeing survey. Issue 1 (2nd January 2021) - Kuhn, Lisa Katharina; Fletcher, Lydia; Bradshaw, Sally
ABSTRACT: Background : The decline of young people's wellbeing in the UK and elsewhere has become an increasing focus for attention. In this context, it is encouraging to note some evidence suggesting that participation in extracurricular activities may have potential to improve wellbeing. However, the considerable conceptual and methodological challenges involved in the measurement of constructs within this non-traditional assessment domain should be recognised. Purpose : Against this backdrop, we report on the development of a survey to measure the contribution of taking part in extracurricular activities on young people's subjective wellbeing and associated soft skills. Methods : Participants (N = 4, 638) were a sample of young people enrolled in a well-known extracurricular award programme in the UK: The Duke of Edinburgh's Award (DofE). They completed a self-report survey which had been developed to address key areas relevant to the DofE and wellbeing, such as: resilience and overcoming adversity, confidence and self-esteem, and working with others and communication. Data were analysed quantitatively. Findings : Factor analysis confirmed a reliable three-factor structure of the measure, which produced patterns of results comparable to existing research on wellbeing. The identified factors were 'General Wellbeing', 'Resilience and Confidence', and 'Communication (including Leadership and Teamwork)'. Participants largely reported that taking part in DofE activities had improved their wellbeing through increasing confidence, responsibility and their ability to face challenges. Conclusions : We suggest that both the survey outlined here and the process of development could be used to facilitate more reliable and valid measurements of wellbeing and related soft skills outside of traditional classroom settings. The findings, whilst relating here specifically to the DofE in the UK, will be of interest to policymakers, school leaders and educators internationally who are considering what young people need to build and maintain wellbeing, and thus thrive in life.